The Development of Manufacturing Process Analysis: Lesson Learned from Process Mining - Bernardo Nugroho Yahya (Institute of Research and Community Outreach - Petra Christian University, 2014)
Process analysis is recognized as a major stage in business process reengineering that has developed over the last two decades. In the field of manufacturing, manufacturing process analysis (MPA) is defined as performance analysis of the production process. The performance analysis is an outline from data and knowledge into useful forms that can be broadly applied in manufacturing sectors. Process mining, an emerge tool focusing on process perspective and resource perspective, is a way to analyze system based on the event log. The objective of this study is to extend the existing process analysis framework by considering attribute perspective. This study also aims to learn the lessons from some experiences on process mining in manufacture industries. The result of this study will help manufacturing organizations to utilize the process mining approach for analyzing their respective processes.